Association of mitochondrial respiratory chain deficiency in older men with muscle mass and physical performance: findings from the Hertfordshire Sarcopenia Study. (23rd February 2017) - Rygiel, Karolina; Dodds, Richard; Patel, Harnish; Syddall, Holly; Westbury, Leo; Granic, Antoneta; Cooper, Cyrus; Cliff, Joshua; Rocha, Mariana; Turnbull, Doug; Sayer, Avan
Abstract: Background: Sarcopenia has been defined as low muscle mass and physical performance, and recognition of its importance in clinical practice is growing. Declines in muscle mitochondrial function with age have been described although less is known about the role of mitochondrial dysfunction in sarcopenia. The aim of this study was to investigate whether respiratory chain deficiency is associated with muscle mass and physical performance. Methods: Participants were healthy older men from the Hertfordshire Sarcopenia Study. Using immunofluorescence on biopsy samples of the vastus lateralis, we measured concentrations of the NDUFB8 subunit of complex I (C1) and the cytochrome oxidase subunit 1 of complex IV (C4) per fibre. We assessed physical performance using grip strength, walking speed, chair rise time, timed up and go, and standing balance time. We used linear regression with a cluster sandwich estimator to test associations between C1 or C4 and muscle mass and physical performance. Study approval was granted by the Hertfordshire Research Ethics Committee. Findings: Data were available from 77 participants (mean age 72·6 years, SD 2·5). The median number of fibres analysed per participant was 157 (IQR 104–237). We expressed C1 and C4 concentrations as z-scores relative to that expected in young controls. The overall participant mean z-scores were 0·3 (SD 1·3) and −1·5 (0·9) for C1 and C4, respectively. We expressed results of physical performance tests as an aggregate performance score between 0 (worst performance) and 5 (best). Each unit (SD) increase in C1 was associated with an increase in performance score of 0·06 (95% CI 0·02–0·09, p=0·003), whereas the association for C4 did not reach significance. We saw no association between C1 or C4 and muscle mass as measured by dual-energy x-ray energy absorptiometry. Interpretation: We saw marked heterogeneity in C1 and C4, both between and within participants, as well as an apparent age-related decline in C4. The finding of a small but statistically significant positive association between C1 concentrations and physical performance suggests that mitochondrial dysfunction might have a role in the development of sarcopenia. These findings will help inform the design of future studies across a wider range of ages in both women and men. Funding: Biotechnology and Biological Sciences Research Council, Medical Research Council, British Geriatrics Society, Wellcome Trust Centre for Mitochondrial Research, National Institute for Health Research Newcastle Biomedical Research Centre in Ageing and Chronic Disease.